Yaygın bir kitle iletişim aracı olarak televizyonun kamusal işlevleri - Erdoğan, Erman (My University, 2008)
YAYGIN BİR KİTLE İLETİŞİM ARACI OLARAK TELEVİZYONUN KAMUSAL İŞLEVLERİ Özellikle, Avrupa 1980’li yıllarda başlayan deregülasyon hareketleri ile yayıncılık alanı özelleşmiş ve devlet tekeli biçiminde sürdürülen bu sistemde özel televizyonlarda yer almaya başlamıştır.Yayıncılık alanının özel sektöre açılmasıyla birlikte “Kültürel bir faaliyet” olarak tanımlanabilecek televizyon yayıncılığında önemli farklılaşmalar kendini göstermiştir.Bu farklılaşmaların başında ise hiç kuşkusuz televizyonlar için reklama dayalı bir yayıncılık anlayışının benimsenmesi gelmektedir.Özel televizyonların reklam gelirlerine dayanan popüler tarzdaki yayıncılığı benimsemesi, kamu hizmeti yayıncılığının etkisini yitirmesine neden olurken, kamu yayıncıları da bu süreçte yayın politikalarında köklü değişiklikler yapmıştır.Bu çalışma ile kamu hizmeti yayıncılığı ile özel televizyonlar arasındaki özsel farklılıklara değinirken, kamu televizyonları ile özel televizyonlar arasındaki rekabetin kamu hizmeti yayıncılığını olumsuz etkilediği görülmüştür.Günümüzde kamu hizmeti yayıncılığında görülen en temel sorun, bu yayıncıların da özel televizyonlardaki gibi popüler tarzda programlar üretmesidir.Türkiye’deki TRT örneğinde olduğu gibi, kamu hizmeti yayıncıları reklama dayalı bir yayıncılık politikası benimsemektedir.Başka bir deyişle kamu hizmeti yayıncılığının kendi

anlamını yitirmesi ve işlevsiz kalması söz konusudur. ABSTRACT THE PUBLIC FUNCTIONS OF THE TELEVISION AS A COMMON MASS MEDIA Especially with the movements of the deregulation which was started in Europe in 1980’s, the broadcasting area was opened to the enterprise and the private televisions have begun taking place in this broadcasting systeam that had been continued as a monopol of the state.With the broadcasting area was opened to the private channels, there has been new differences in the broadcasting, which can be defined as “a cultural activity”.The difference most of all certainly becomes the broadcasting policy which is learnt against the advertisement for the televisions.Because of the commercial television channels considered the popular broadcasting which is learnt against the advertisement, the public service broadcasting has lost its importance and the public broadcasters have started making drastic changes on their broadcasting policy in this process.With this study while the spesific differents are between the public service broadcasting and the commercial broadcasting are being touched on, the rivalry which is among the public televisions and the commercial televisions effected the public broadcasters more than the private broadcasters is appeared as well.On the whole the most fundamental problem which is in the public service broadcasting recently, is this broadcasters product the television programs like the private televisions do.The example of in Turkey within the public service broadcasting channel TRT as well, is appeared that the public service broadcasters considered the broadcasting policy which is supported by advertisement.In other words, it is mentioned that the public service broadcasting will lose its basic meaning and functions.
Keywords: İletişim; Kitle İletişim; Televizyon